Manajemen Kualitas Website Sistem Informasi Desa Berdasarkan Model FURPS Menggunakan Metode Euclidean Distance - Dimas Aswito; Rica Rahmahidayatul; Rani Purbaningtyas; Sholihah Ayu Wulandari (Jurnal Teknologi Informasi dan Terapan, 2024)
The importance of software testing is very prominent in the software development stage. Software testing is an important aspect that cannot be ignored to ensure the quality of an application. One example is testing dynamic web pages such as the one that will be the main focus of the research, namely the Ketapanrame Village Website. Testing of the Ketapanrame Village Website was carried out thoroughly on various aspects, including feature functionality and web appearance aesthetics, to ensure compliance with the specified specifications. In order to achieve satisfactory results from testing, there are feature elements on the web page that will be tested using the FURPS model standard. Each indicator from the FURPS model has a special role in ensuring the overall quality of the software by involving the participation of respondents to find the average value. The challenge arises in finding an appropriate average value for testing such web pages. To overcome this problem, this research is distributing questionnaires to find values from respondents and will calculate the average value using the Euclidean Distance method. This concept was chosen because it has been proven to provide optimal average values. The test results show that the combination of the FURPS model and the Euclidean Distance calculation method provides satisfactory results. Combination suitability is not easy to do, especially in the part of finding the average value which must involve many parties to achieve optimal results.